Determine the Effect of Risk Management Disclosures in Consumer Goods Manufacture Companies with The Analysis of Firm Size, Leverage, and Managerial Ownership - Leny Suzan; Nabila Choirunnisa (International Journal of Economics Development Research (IJEDR), 2023)
This research objective to analyze whether risk management disclosure in the consumer goods sector of manufacture companies that are listed on the Indonesia Stock Exchange (IDX) on 2019-2021 period can be influenced by firm size, leverage, and managerial ownership. A quantitative research method was employed using data that was cumulated from annual reports of 50 manufacture companies, specifically the consumer goods sector that is listed on the IDX. Based on the conduction tests, it is known that risk management disclosure is not influenced by firm size and managerial ownership partially, while leverage has a significant negative influence on risk management disclosure. However, when these three variables are used together, they have a significant influence on risk management disclosure by the companies. This research provides valuable insights for investors to consider risk management disclosure as an important factor. Therefore, future research can further develop this study by using more representative variables and considering external factors that may affect risk in consumer goods manufacture companies.